Managing Financial Resources - Broadbent, Michael; Cullen, John, 1951-; Institute of Management (Great Britain) (Oxford : Butterworth-Heinemann, 1997)
This book is designed to provide the underpinning knowledge and understanding required for any competency-based management course. It is based upon the Management Charter Initiative's Occupational Standards for Management NVQs and SVQs.
"Published in association with the Institute of Management".
Includes bibliographies and index.
Keywords: Business enterprises -- Finance; Management; Managerial accounting